Mekanisme Pembiayaan Produk Gadai Emas Pada PT. Bank Syariah Indonesia KC Purworejo - M. Nailul Author; Ririn Makrifah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The development of the sharia financial system is marked by the establishment of various sharia institutions and the issuance of various sharia-based financial instruments. Bank Syariah Indonesia is a financial institution that mediates the needs of the community through the various products and services it has. Bank Syariah Indonesia is one of the banks that has a gold pawn product which is considered successful because it continues to increase every year. The product owned by Bank Syariah Indonesia KCP Purworejo is a pawn financing product (gold rahn) which is financing for productive and consumptive needs provided to all groups who need funds with gold as the margin. This research aims to determine the mechanism of gold pawning products at Bank Syariah Indonesia and the constraints and barriers faced by banks in financing gold pawning at BSI. This research uses a qualitative research method, in which the researcher will describe or describe the mechanism of gold pawning products at Bank Syariah Indonesia KCP Purworejo. Based on the research results, it was found that the gold pawn product mechanism at Bank Syariah Indonesia has implemented a service system that is easy, fast, cheap and safe and is in accordance with the DSN MUI Fatwa No.25/DSN-MUI/III/2002 dated 26 June 2002 concerning rahn which explains the provisions of pawning practices in accordance with Islamic law. One of them is "the amount of maintenance and storage costs for marhun should not be determined based on the loan amount". Apart from that, it is very easy to apply with the requirements for gold, KTP and NPWP if the financing is above IDR 50,000,000. In inputting customer data, Sharia Bank processes via the PWG Monitoring application to facilitate the disbursement process without having to directly review the customer's whereabouts because the guarantee is already in the hands of BSI. Then, the obstacles and constraints faced in financing gold pawning at BSI KCP Purworejo are in terms of the reach of promoting gold pawning products, from the customer's economic perspective, and also in terms of forgetting payment due dates.